Is retrograde drilling really useful for osteochondral lesion of talus with subchondral cyst?: A case report. Issue 49 (December 2016) - Jeong, Seong-Yup; Kim, Jong-Kil; Lee, Kwang-Bok
Abstract: Rationale: Retrograde drilling is a well accepted procedure for osteochondral lesion of the talus and subchondral cyst with intact overlying cartilage. It has good results in most reports. Compared to anterograde drilling, retrograde drilling can protect the integrity of the articular cartilage. The purpose of this study was to evaluate the suitability of using retrograde drilling for osteochondral lesion with subchondral cyst and discuss the mechanism involved in the development of subchondral cyst. Patient concerns: We report a 53-year-old man who had complained left ankle pain that lasted over 6 months which was exacerbated by walking. Diagnoses: We diagnosed it as osteochondral lesion of the talus with subchondral cyst. Interventions: Plain X-ray, computed tomography, and magnetic resonance imaging (MRI) of the ankle. Outcomes: He undertook retrograde drilling without debridement of cartilage. After the surgery, the pain had been subsided for 1 year, although arthritic change had progressed. However, after 5 years of retrograde drilling, he revisited our hospital due to severe ankle pain. Plain X-ray and MRI showed arthritic change of the ankle and multiple cystic formation of talus. Lessons: Retrograde drilling has some problem because this procedure is not theoretically correct when the development of a subchondral cyst in osteochondral lesion of the talus is considered. In addition, retrograde drilling may impair uninjured bone marrow of the talus, resulting in the development of multiple cystic formations.